The Prodigal Daughter - Archer, Jeffrey (New York HarperPaperbacks, 1993)
The stunning sequel to Kane & Abel. Florentyna, daughter of a powerful Chicago baron, and Richard, son of a blue-blooded millionaire, were never supposed to meet and fall in love--because their fathers were bitter enemies. This blazing novel spans half a decade and moves from Chicago to New York, Boston to Washington.
English Fiction.
Keywords: United States -- Businesswomen -- Children of immigrants